Problematika Evaluasi dalam Pembelajaran BIPA Tingkat Madya: Studi Kualitatif di Universitas Walailak, Thailand - Mahardhika Agung Wicaksono; Ahmad Jami’ul Amil; Siti Mutiatun (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
Evaluation plays a crucial role in Indonesian as a Foreign Language (BIPA) learning, particularly at the intermediate level, which represents a transitional stage from basic language acquisition toward pragmatic, cultural, and academic language competence. This qualitative study aims to identify and analyze evaluation issues based on teaching materials and learning materials for intermediate-level BIPA at Walailak University, Thailand. The research method used a case study approach with data collection techniques through participatory observation, in-depth interviews with three BIPA teachers, document analysis (syllabus, lesson plans, evaluation sheets, and teaching materials), and focus group discussions with 15 intermediate level students. The findings reveal four main problems: (1) the gap between teaching materials and evaluation instruments; (2) the dominance of product-based summative evaluation over process-based evaluation; (3) challenges in evaluating pragmatic and cultural competencies; and (4) limitations in contextualizing evaluation materials to the Thai reality. These problems stem from the limited availability of teaching materials, the administrative burden on teachers, and the need for more specific assessment training for the Thai context. This study recommends the development of a continuous assessment model integrated with teaching materials based on the local Thai context, as well as assessment literacy training for BIPA teachers.